Rancang Bangun Door Lock dan Alarm Pintu Kantor Berbasis Sidik Jari - Dinda Triani; Evi Andrika; Intan Rahayu; Putri Ramadhani Br. Sembiring; David JM. Sembiring; Sri Novida Sari; Nirwan Sinuhaji (JISTI: Jurnal Ilmu Komputer, Sistem Informasi dan Teknologi Informasi, 2025)
The development of technology and industrial automation encourage humans to meet their needs quickly. So that technology was developed to help and ease human work in the future, the automatic door lock system with Arduino Uno-based fingger print is a system created to replace the role of conventional keys. This tool has the ability to detect the correct fingerprint automatically this system is connected to the power supply, namely the adapter, the adapter is connected to the Arduino Uno which has been channeled with all components that have been connected to the pin, such as solenoid door lock, LCD, alarm and relay. Using a single fingerprint sensor, solenoid door lock as unlock, LCD and alarm are useful for Arduino interfaces and microcontrollers as the brain of these systems and programming applications.